Political marketing principles and applications - Lees-Marshment, Jennifer (Routledge, 2019)
Substantially revised throughout, the third edition of Political Marketing continues to offer students the most comprehensive introduction to this rapidly growing field. It provides an accessible but in-depth guide to what political marketing is and how it is used in practice and encourages reflection on how it should be used in the future. New Features and benefits of the third edition: Fully updated throughout with new research on emerging practices in the field and ethical implications such as the use of big data, authenticity and the limitations of voters as consumers in light of Brexit; A new employability section on political marketing in the workplace; Extensive pedagogical features including new peer-reviewed case studies, democratic debates, and fully updated practitioner perspectives, best practice guides, and class discussion points and assessments. Led by a leading expert in the field and including contributions from other key academics in the field, this textbook is essential reading for all students of political marketing, parties and elections, and comparative politics